2013
DOI: 10.3109/1547691x.2013.804134
|View full text |Cite
|
Sign up to set email alerts
|

Potential for amelioration of aflatoxin B1-induced immunotoxic effects in progeny of white leghorn breeder hens co-exposed to vitamin E

Abstract: This study was designed to evaluate the protective activity of Vitamin E (Vit E) on the immunotoxic effects induced by aflatoxin B1 (AFB1) in the progeny of breeder hens. For this purpose, 192 White Leghorn (WL) layer breeder hens were divided into 12 groups (A-L) and then fed test diets for either 1, 2 or 3 weeks. Group A was kept on basal feed (2900 Kcal/kg metabolizable energy) and served as control, while group B was offered a feed supplemented with Vit E at 100 mg/Kg. Groups C-G were offered feed containi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 30 publications
1
11
1
Order By: Relevance
“…Interdigital administration of PHA could stimulate T-lymphocyte with a slight effect on B-lymphocytes (Raju & Devegowda, 2002). Birds fed with mycotoxins had lower antibody titers, compared to other birds (Khan et al, 2014). The lower immune responses in AFB1 may be due to the prevention of protein synthesis, which decreases IgG and IgA production (Sur & Celik, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interdigital administration of PHA could stimulate T-lymphocyte with a slight effect on B-lymphocytes (Raju & Devegowda, 2002). Birds fed with mycotoxins had lower antibody titers, compared to other birds (Khan et al, 2014). The lower immune responses in AFB1 may be due to the prevention of protein synthesis, which decreases IgG and IgA production (Sur & Celik, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported as a 21% reduction in body weight of broilers fed with 300 µg/kg AFB1 in their diet (Raju & Devegowda, 2002). It has been shown that birds receiving mycotoxins have lower antibody titers (Girish et al, 2008;Khan et al, 2014). Studies have also shown that aflatoxin-contaminated diets may cause biochemical and physiological damage to the liver (Gowda et al, 2008;Rezaret al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An effective approach for detoxification of mycotoxin in animal feedstuff is the usage of nutritionally inert substances, which can minimize the level of toxicity. Toxin binders, such as aluminosilicate, yeast, lactic acid producing bacteria and detoxifying agents such as vitamin E, are used in the feed to reduce the harmful effects of these mycotoxins on poultry birds 2014a;Chen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…AFB1 has been identified as group 1 carcinogenic agent by the International agency for research on cancer (IRAC). In livestock and poultry, AFB1 is considered as potent hepatotoxic and nephrotoxic agent causing immunosuppressive, mutagenic and teratogenic effects (Hassan et al, 2012;Khan et al, 2014). In poultry industry aflatoxicosis is considered an important issue by virtue of its occurrence and toxicities (Saleemi et al, 2015).…”
Section: Introductionmentioning
confidence: 99%